Mistaken identity - Scottoline, Lisa. (New York, NY : HarperCollins, 1999)
Life holds few surprises for Bennie Rosato, head of her own Philadelphia law firm. As a criminal attorney now specializing in police misconduct cases, she's seen the noblest and most deviant aspects of human nature. But nothing can prepare her for the moment she enters a maximum-security prison to meet her new client, Alice Connolly, face to face. Accused of brutally murdering her lover, a highly decorated police dtective, Connolly claims the police framed her.
1 3 7 9 11 12 13 17 18 19 25 26 30 33 34 36 39
Keywords: Rosato & Associates (Imaginary organization) -- Fiction